Health Services for Health Social Security Administrative Body Participants at the Hingk Health Center, West Papua Province, Indonesia - Marsumiyanto, Marsumiyanto; Annisa, Nur; Alim, Andi; Oruh, Shermina; Rusnita, Rusnita; Zainuddin, Zainuddin (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: To improve services for members of the Social Security Administrative Body at the Hingk Community Health Center in West Papua Province, it is highly hoped that the leadership of the Community Health Center can improve services for participants of the Health Social Security Administering Body. This study aims to obtain information about the services of members of the Health Social Security Administration at the Hingk Community Health Center, West Papua Province, Indonesia.Subjects and Method: This study uses a qualitative descriptive approach. In this study, the authors used two key informants and main informant to dig for indepth information related to health services in terms of waiting time, health service facilities and payment mechanisms for members of the Social Security Administering Body in the working area of the Hingk Health Center. The instrument used by researchers in collecting data is the researchers themselves. The types of data and data sources that the researchers will collect in this study consist of primary data and secondary data. Data collection techniques were carried out through observation, in-depth interviews and documentation. While the stages of qualitative data analysis were carried out by researchers with three stages of the process, namely data reduction, data categorization, and data interpretation.Results: The results of the study illustrate that the level of service for members of the Social Security Administering Body at the Hingk Community Health Center in West Papua Province, waiting time, and facilities are still relatively low for services for participants of the Health Social Security Administering Body. This was revealed during in-depth interviews that most of the patients of the Health Social Security Administering Body waited a long time to be examined, and patients were dissatisfied with the facilities provided by health workers.Conclusion: The long waiting time for patient examinations would cause complaints from patients and the lack of availability of facilities provided by the Public Health Center would cause patients to feel less satisfied with the services provided.Keywords: waiting time, service facilities, financing mechanismsCorrespondence:Nur Annisa. Faculty of Public Health, University of Pejuang Republic Indonesia. Jl. Raya Baruga, Antang Village, Manggala District, Makassar City, South Sulawesi 90234. Email: nurannissa135@gmail.com. Mobile: +6282149539044.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.02.05